Towards a Process for Negotiation of E-contracts Involving Web Services - Silva, Gabriel Costa; Gimenes, Itana M. de Souza; Fantinato, Marcelo; de Toledo, Maria B. Felgar (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2012)
Organizations involved in cooperative business processes have different interests and points of view. A negotiation allows them to discuss their interests and requirements in order to reach an acceptable agreement. We propose an integrated web service negotiation process that considers human interaction and the use of different protocols. It focuses on the application of feature modelling to describe the negotiated services. Our contributions include: (i) the definition of a negotiation process; (ii) the definition of a conceptual model to support the negotiation of web services; (iii) reuse of artefacts generated throughout the negotiation process; and (iv) coverage of critical elements in the negotiation of electronic contracts.